2006
DOI: 10.1302/0301-620x.88b7.17468
|View full text |Cite
|
Sign up to set email alerts
|

Computer navigation of the acetabular component

Abstract: Our aim was to assess the intra- and inter-observer reliability in the establishment of the anterior pelvic plane used in imageless computer-assisted navigation. From this we determined the subsequent effects on version and inclination of the acetabular component. A cadaver model was developed with a specifically-designed rod which held the component tracker at a fixed orientation to the pelvis, leaving the anterior pelvic plane as the only variable. Eight surgeons determined the anterior pelvic plane by palpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 9 publications
3
41
0
5
Order By: Relevance
“…For example, subtle differences for ASIS referencing would not alter anteversion considerably as long as these points remained in the APP. Spencer et al [35], however, reported higher variation for anteversion than for inclination, and substantial interobserver variability.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…For example, subtle differences for ASIS referencing would not alter anteversion considerably as long as these points remained in the APP. Spencer et al [35], however, reported higher variation for anteversion than for inclination, and substantial interobserver variability.…”
Section: Discussionmentioning
confidence: 95%
“…Only one cadaver was used. However, published studies and our prior study used only limited numbers of cadaver specimens [17,29,35,38,40]. In clinical practice, there undoubtedly would be more variability for imageless referencing if more specimens would have been used.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations